Effects of Juniperus phoenicea Hydroalcoholic Extract on Inflammatory Mediators and Oxidative Stress Markers in Carrageenan-Induced Paw Oedema in Mice. (9th July 2018) - Zouari Bouassida, Karama; Makni, Samar; Tounsi, Amina; Jlaiel, Lobna; Trigui, Mohamed; Tounsi, Slim
Abstract : Juniperus phoenicea ( J. phoenicea ) is a wild tree belonging to the Cupressaceae family, commonly used for the treatment of several disorders. This study aimed to evaluate the potential protective effects of J. phoenicea hydroethanolic extract (EtOH-H2 OE) against oxidation, acute inflammation, and pain in mice models. For the purpose, chemical compounds of J. phoenicea EtOH-H2 OE were also analyzed by GC-MS. The J. phoenicea EtOH-H2 OE showed a potent antioxidant activity in vitro, thanks to its richness in phenolic and flavonoid compounds. Mice treated with EtOH-H2 OE (100 mg/kg BW) showed reduced paw oedema formation and decreased malondialdehyde (MDA) content. The evaluation of antioxidant enzyme activities in paw oedema tissue after five hours of carrageenan induction showed a significant increase (P < 0.05 ). Inflammatory biomarkers explorations of J. phoenicea EtOH-H2 OE-treated mice showed a restoration of the studied parameters to near-normal values. Furthermore, EtOH-H2 OE of J. phoenicea produced a significant reduction of the number of abdominal writhes (P < 0.05 ) in a dose-dependent way. Phytochemical analysis of the J. phoenicea EtOH-H2 OE by GC-MS showed the presence of hexadecanoic and stearic acids known as anti-inflammatory and analgesic compounds. Our investigation provided evidence that J. phoenicea EtOH-H2 OE can effectively reduce the inflammation and pain in mice models.